2011
DOI: 10.1007/s10695-011-9527-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tissue-specific effect of cadmium on antioxidant defense system and lipid peroxidation in freshwater murrel, Channa punctatus

Abstract: The effects of different concentrations of cadmium chloride on the extent of lipid peroxidation (LPO) and alterations in the antioxidant enzyme activities were studied in liver, kidney and gill tissues of freshwater murrel, Channa punctatus. The fish specimens were exposed to 6.7, 13.4 and 20.1 mg l(-1) sublethal concentrations of cadmium chloride and the oxidative stress was assessed after 24, 48, 72 and 96 h post-exposure. The biomarkers selected for the study were thiobarbituric acid reactive substances for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 73 publications
(64 reference statements)
7
30
1
Order By: Relevance
“…On the other hand, LPx levels were significantly enhanced in these tissues of fishes exposed to Cd alone or in combination with AH infection. The results are in consonance with previous reports (26)(27)(28). It is well known that Cd severely affects structural and functional integrity of tissues through oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, LPx levels were significantly enhanced in these tissues of fishes exposed to Cd alone or in combination with AH infection. The results are in consonance with previous reports (26)(27)(28). It is well known that Cd severely affects structural and functional integrity of tissues through oxidative stress.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies reported that additives in fish feed decreased the amounts of GOT and GPT (Ji et al, ; Kesbic, Acar, Yilmaz, & Aydin, ; Rao, Das, Jyotyrmayee, & Chakrabarti, ; Shalaby, Khattab, & Abdel Rahman, ). GPx, which is a protective antioxidant, acts along with CAT to deactivate the negative effects of ROS by scavenging hydrogen peroxide and other peroxides (Dabas et al, ). In our study, the amount of GPx did not change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cd can compete with essential metals for protein-binding sites (Pruski and Dixon, 2002), inducing the release of Fe 2+ and Cu 2+ ions and increasing the production of ROS (Xu et al, 2011). In general, the Cd 2+ exposure elevated the lipid peroxidation in subject tissues and modulated the activities of SOD or other antioxidant defense systems as well (Dabas et al, 2011). In our research, the expression level of SOD which was particularly higher in the experimental group than in the control increased with the Cd 2+ concentration ranging from 0.2 to 5 mM in the medium.…”
Section: Discussionmentioning
confidence: 99%